Letter to the editor: Analysis of stroke patient migration for mechanical thrombectomy and changes in neurointerventional center size in Germany - Weber, Ralph; Bartig, Dirk; Krogias, Christos; Richter, Daniel; Hacke, Werner; Eyding, Jens (Neurological research and practice, 2021)
AIM AND METHODS: To analyse nationwide changes in neurointerventional center size of all German hospitals performing mechanical thrombectomy (MT) in stroke patients from 2016 to 2019. Furthermore, we assessed cross-district patient migration for MT for the first time using hospitals' structured quality reports and German Diagnosis-Related Groups data in 2019. FINDINGS: Number of hospitals performing more than 100 MT procedures/year doubled in Germany from 2016 (n = 36) to 2019 (n = 71), and these neurointerventional centers performed 71% of all MT procedures in 2019. The overall increase in MT procedures was largely driven by these high-volume neurointerventional centers with ability to perform MT 24/7 (121% increase as compared with 8% increase in hospitals performing less than 100 MT procedures/year). The highest cross-district patient mobility/transfer of stroke patients for MT was observed in districts adjacent to these high-volume neurointerventional centers with existing neurovascular networks. CONCLUSION: The substantial increase in MT procedures observed in Germany between 2016 and 2019 was almost exclusively delivered by high-volume stroke centers performing more than 100 MT procedures per year in established neurovascular networks. As there is still a reasonable number of districts with low MT rates, further structural improvement including implementation of new or expansion of existing neurovascular networks and regional tailored MT triage concepts is needed.